Hyaluronic Acid-Modified and Doxorubicin-Loaded Au Nanorings for Dual-Responsive and Dual-Imaging Guided Targeted Synergistic Photothermal Chemotherapy Against Pancreatic Carcinoma - Hu L; Song Z; Wu B; Yang X; Chen F; Wang X (International Journal of Nanomedicine)
Lingyu Hu,* Zhengwei Song,* Bin Wu, Xiaodan Yang, Fei Chen, Xiaoguang Wang Department of Surgery, The Second Affiliated Hospital of Jiaxing University, Jiaxing, 314000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Chen; Xiaoguang Wang, Department of Surgery, The Second Affiliated Hospital of Jiaxing University, No. 1518, Huancheng North Road, Jiaxing, 314000, People’s Republic of China, Tel +86-0573-82080930, Email tangchouer@163.com; wangxiaoguang@zjxu.edu.cnIntroduction: Pancreatic carcinoma (PC) is a highly malignant digestive tumor. Nanotechnology-based minimally invasive techniques have been proposed to provide a new opportunity for PC treatment.Methods: A minimally invasive nanoplatform (named HA/DOX-AuNRs) is fabricated by HA modifying and DOX loading Au nanorings (AuNR). Because of their complicated geometric structure and tunable localized surface plasmon resonance peak in the second near-infrared laser window (NIR-II window), HA/DOX-AuNRs exhibit fluorescence/photoacoustic and photothermal properties, dual-responsive DOX release, and tumor-targeting ability. HA/DOX-AuNRs are expected to improve the tumor therapeutic efficiency and reduce undesirable side effects through fluorescence/photoacoustic dual-imaging guided targeted synergetic photothermal chemotherapy under NIR-II irradiation.Results: The morphological and physicochemical properties of HA/DOX-AuNRs are well-examined at first. The cytotoxicity, cellular uptake, and in vitro therapeutic effect of fluorescence/photoacoustic dual-imaging guided targeted synergetic photothermal chemotherapy are evaluated in Panc-1 cells. The in vivo biodistribution, anticancer effects, and systemic toxicity are investigated using PC xenograft models.Discussion: HA/DOX-AuNRs significantly improve the therapeutic efficacy in a dual-responsive and dual-imaging guided targeted synergy.Kewords: pancreatic carcinoma, Au nanorings, DOX, NIR-II, photothermal therapy, chemotherapy